The BaSICS (Baby Skin Integrity Comparison Survey) study: A prospective experimental study using maternal observations to report the effect of baby wipes on the incidence of irritant diaper dermatitis in infants, from birth to eight weeks of age - Alan D. Price; Jeanne Lythgoe; James Ackers-Johnson; Penny A. Cook; Alexandra M. Clarke-Cornwell; Fiona MacVane Phipps (Elsevier, 2021)
Background: Baby wipes have been shown to be safe and effective in maintaining skin integrity when compared to the use of water alone. However, no previous study has compared different formulations of wipe. The aim of the BaSICS study was to identify any differences in incidence of irritant diaper dermatitis (IDD) in infants assigned to three different brands of wipe, all marketed as suitable for neonates, but which contained varying numbers of ingredients. Methods: Women were recruited during the prenatal period. Participants were randomly assigned to receive one of three brands of wipe for use during the first eight weeks following childbirth. All participants received the same nappies. Participants reported their infant's skin integrity on a scale of 1-5 daily using a bespoke smartphone application. Analysis of effect of brand on clinically significant IDD (score 3 or more) incidence was conducted using a negative binomial generalised linear model, controlling for possible confounders at baseline. Analysts were blind to brand of wipe. Results: Of 737 women enrolled, 15 were excluded (admitted to neonatal intensive care, premature or other infant health issues). Of the 722 eligible babies, 698 (97%) remained in the study for the full 8-week duration, 24.6% of whom had IDD at some point during the study. Mothers using the brand with the fewest ingredients reported fewer days of clinically significant nappy rash (score≥3) than participants using the two other brands (p = 0.002 and p < 0.001). Severe IDD (grades 4 and 5) was rare (2.4%). Conclusions: Rarity of severe IDD suggested that sensitive formula baby wipes are safe when used in cleansing babies from birth to eight weeks during nappy changes. The brand with fewest ingredients had significantly fewer days of clinically significant IDD. Daily observations recorded on a smartphone application proved to be a highly acceptable method of obtaining real-time data on IDD. Clinical Trial registration: This study was not designed or registered as a clinical trial as no intervention in normal patterns of infant care took place. Mothers who had already decided to use disposable nappies and a baby wipe product agreed to observe and report on their infants' skin condition; in return they received a 9-week supply of free nappies and wipes.